Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32‐channel phased‐array head coil: Application to patients with secondary progressive multiple sclerosis. (9th August 2022) - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena V.; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Doerfler, Arnd; Nagel, Armin M.; Schmidt, Manuel
Abstract : Apparent tissue sodium concentrations (aTSCs) determined by 23 Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal‐to‐noise ratio of 23 Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23 Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23 Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual‐tuned 23 Na/ 1 H birdcage coil with a receive‐only 32‐channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired‐samples Wilcoxon rank‐sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS ( p  = 0.42). The proposed quantification workflow for 23 Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group ( p  = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients ( p  = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23 Na brain MRI as a biomarker in diseases such as MS. Abstract : The accuracy and reliability of quantitative 23 Na brain MRI was improved by implementing a dedicated postprocessing pipeline. Sodium concentrations of brain tissues were determined in healthy subjects and patients with MS. Signal intensities were normalized using the mean cerebrospinal fluid sodium concentration determined in separate patients receiving a spinal tap. The proposed approach shows high repeatability, and the results can serve as a baseline for further studies establishing 23 Na brain MRI as a biomarker in diseases such as MS.